2020
DOI: 10.4293/jsls.2020.00007
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Abdominal Wall Hernia Repair

Abstract: Background and Objectives: The aim of this retrospective monocentric study was to evaluate results and recurrence rate with long-term follow-up after laparoscopic incisional/ventral hernia repair. Methods: This was a retrospective, single-center, observational trial, collecting data from patients who underwent laparoscopic incisional/ventral abdominal hernia repair using the open intraperitoneal onlay mesh technique and a single mesh type. All patients signed an informed consent form before surgery. Results: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…The mean age of our patients was 36.8 years old which is significantly different than what was reported in international studies 53.3 years (yet it was comparable with a study that was conducted in Egypt 44.8 years old. 6,7 The female to male gender occurrence ratio was 3.3:1 in the presented study which is higher than ratios reported in other international studies 1.3:1. 6 However, previous data from studies done in Egypt (5:1) are comparable to ours.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…The mean age of our patients was 36.8 years old which is significantly different than what was reported in international studies 53.3 years (yet it was comparable with a study that was conducted in Egypt 44.8 years old. 6,7 The female to male gender occurrence ratio was 3.3:1 in the presented study which is higher than ratios reported in other international studies 1.3:1. 6 However, previous data from studies done in Egypt (5:1) are comparable to ours.…”
Section: Discussioncontrasting
confidence: 78%
“…In agreement with international study, abdominal wall surgery was the most associated risk factor in the development of ventral hernia and this is elaborated more in an 11-years follow up study that was conducted in the United States of America composed of 420 patients found that abdominal wall surgery was the most common risk factor for the development of hernia. 7 In the present study, para umbilical hernias were the most common operated hernia (144 hernia) followed by umbilical (110 hernia), and incisional (87 hernia). However, it was found in a previous study that was done in the United Kingdom that the umbilical hernia was the commonest followed epigastric, and incisional hernias.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Injuries to the inferior epigastric arteries, femoral nerve, genito-femoral nerve, and lateral cutaneous nerve of the thigh were the most frequently reported consequences. Due to adhesion between the viscera and the utilized tacks, certain studies have observed colonic and small intestinal fistula, which can cause severe pain and may require surgical intervention (5) .…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of concomitant diseases in elderly patients will increase the risk of complications and death in surgery. [9][10][11][12] Complications at some stage because of reluctance for operation and it has been pointed out in many studies that the mortality and morbidity increase many folds if such hernias are operated in an emergency in elderly patients. [13][14][15][16][17] Comorbidities with the presence of…”
mentioning
confidence: 99%